2021
DOI: 10.3390/pharmaceutics13030321
|View full text |Cite
|
Sign up to set email alerts
|

Liposomes as a Nanoplatform to Improve the Delivery of Antibiotics into Staphylococcus aureus Biofilms

Abstract: Staphylococcus aureus biofilm-associated infections are a major public health concern. Current therapies are hampered by reduced penetration of antibiotics through biofilm and low accumulation levels at infected sites, requiring prolonged usage. To overcome these, repurposing antibiotics in combination with nanotechnological platforms is one of the most appealing fast-track and cost-effective approaches. In the present work, we assessed the potential therapeutic benefit of three antibiotics, vancomycin, levofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 72 publications
(54 reference statements)
3
33
0
Order By: Relevance
“…Several other reports have also proved in vitro and in vivo (in some cases) the superior anti-biofilm activity of liposomal drugs. It was indeed proposed that the reduced penetra-tion of antibiotics through biofilm and low accumulation at infected sites can be overcome by nanotechnological platform approaches [53]. In this context, cationic liposomes were found to have a high anti-biofilm effect and prolonged retention on P. aeruginosa biofilm, and anionic liposomes showed high permeability in the biofilms.…”
Section: Antibiofilm Activity Of Mox Liposomes-effect Of Liposomes Pr...mentioning
confidence: 99%
“…Several other reports have also proved in vitro and in vivo (in some cases) the superior anti-biofilm activity of liposomal drugs. It was indeed proposed that the reduced penetra-tion of antibiotics through biofilm and low accumulation at infected sites can be overcome by nanotechnological platform approaches [53]. In this context, cationic liposomes were found to have a high anti-biofilm effect and prolonged retention on P. aeruginosa biofilm, and anionic liposomes showed high permeability in the biofilms.…”
Section: Antibiofilm Activity Of Mox Liposomes-effect Of Liposomes Pr...mentioning
confidence: 99%
“…If the biofilm involves a multidrug-resistant strain such as methicillin resistant Staphylococcus aureus (MRSA), the infection may become chronic and even untreatable. Nevertheless, in vitro and in vivo studies have demonstrated improved efficacy of liposomal formulations against biofilm associated MRSA infections [69,103,104]. In particular, a liposomal formulation co-loaded with vancomycin and ciprofloxacin allowed complete sterilization of the bone in a S. aureus osteomyelitis model, showing this strategy has high therapeutic potential against these life-threatening infections [105].…”
Section: Overcoming Bacterial Resistance Mechanismsmentioning
confidence: 99%
“…As shown in several studies, nanoscale size allows for the nanoparticles to penetrate microbial cell walls and biofilms layers, causing several events such as irreversible damage of microbial membranes [ 9 , 117 , 118 ]. Several hypotheses for nanoparticles mechanisms of action have been explored, including cell membrane alterations and disruption [ 119 , 120 ], ROS generation, and lipid peroxidation [ 121 , 122 , 123 ].…”
Section: Antibacterial and Antibiofilm Strategiesmentioning
confidence: 99%
“…This increased resistance can be attributed to different factors, including decreased diffusion of antimicrobial agents through the self-produced extracellular matrix (made of polysaccharides, nucleic acids, and proteins matrix) [ 8 , 9 , 10 ], altered metabolic activity, and formation of persister cells [ 11 ]. Moreover, a relevant characteristic of biofilms is the fact that bacteria are able to inter-communicate and collaborate to survive in even the hardest conditions.…”
Section: Introductionmentioning
confidence: 99%